Formulasi Model Safety Stock dan Reorder Point untuk Berbagai Kondisi Persediaan Material - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
Inventory is an asset, but inventory is an low liquidity asset. Inventory of material (raw material, spare parts, consumables, etc.) requires special handling techniques that are different from the techniques of work in process or finished goods, because the material supply comes from suppliers who are outside the company's environment, it can be deterministic or probabilistic/ stochastic, so that requires different handling techniques. The parameters that must be considered in handling material inventories, such as the level of demand and leadtime generally variable because they are influenced by external conditions that are beyond the control of the company. This research is an analytical study based on literature review which aims to formulate a model of inventory control, especially safety stock and reorder point by taking into account both fixed and variable demand and leadtime parameters. Description of conditions is needed to obtain a model formulation that is suitable for these conditions. Model testing is done using artificial data. The result of the study were in the form of a safety stock and reorder point formula. The result of the study indicate that the formula for determining the level of safety stock and reorder point has a variety of models according to their respective condition, so that the condition needs to be identified first before determining the appropriate model to use. If the company wants to reduce its inventory level, the company must control the demand and the leadtime.